2008
DOI: 10.1002/biot.200800005
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial pAL2‐1 plasmid homologs are senescence factors in Podospora anserina independent of intrinsic senescence

Abstract: Since the first description of a linear mitochondrial plasmid in Podospora anserina, pAL2-1, and homologous plasmids have gone from being considered beneficial longevity plasmids, via neutral genetic elements, toward mutator plasmids causing senescence. The plasmid has an invertron structure, with terminal inverted repeats and encodes a DNA and a RNA polymerase. Here we test whether pAL2-1 homologs cause rapid aging independent of intrinsic and external conditions. We first analyzed a natural population of P. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…The P. anserina laboratory strains were all derived from strain S and have been described (15,42). The natural P. anserina isolates were collected by growing mycelium from fragments of herbivore feces collected on fields around Wageningen, The Netherlands, since 1991 and were stored at −80°C (37,43). Spores were collected from emerging P. anserine-like fruiting bodies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The P. anserina laboratory strains were all derived from strain S and have been described (15,42). The natural P. anserina isolates were collected by growing mycelium from fragments of herbivore feces collected on fields around Wageningen, The Netherlands, since 1991 and were stored at −80°C (37,43). Spores were collected from emerging P. anserine-like fruiting bodies.…”
Section: Methodsmentioning
confidence: 99%
“…Forty percent of our P. anserina isolates were found to be infected with pAL2-1, a mitochondrial senescence plasmid that reduces the lifespan of P. anserina under all conditions tested (37). We combined these data with our het-s genotyping data and found 37 of the 72 het-s isolates and 8 of the 40 het-S isolates carried the plasmid, (Fig.…”
Section: Role Of Het-s/het-s On Transmission Of a Deleterious Senescencementioning
confidence: 98%
See 1 more Smart Citation
“…In the ascomycete Podospora, it has been suggested that strains acquire integrations of a mitochondrial plasmid pAL2-1 into favorable, neutral, or unfavorable locations of the mitochondrial genome, and thus, these strains show variable phenotypes for enhanced or reduced lifespan (van Diepeningen et al 2008). The mF plasmid also recombines with the mitochondrial genome (Fig.…”
Section: Conformational Change Of the Mitochondrial Genome With Mfmentioning
confidence: 99%
“…We have analysed the size of the WD domain of the het-r locus in a sample of ten natural isolates of P. anserina randomly chosen from a collection already described (van der Gaag et al 2000;van Diepeningen et al 2008) or retrieved from the CBS (Centraal Bureau voor Schimmelcultures, Utrecht, The Netherlands), thereby extending our previous analysis of natural isolates from France ). The number of WD40 repeats was deduced from the size of the WD repeat domain amplicons, and are reported in Table 2.…”
Section: The Het-r Locus Is Polymorphic In Natural Isolatesmentioning
confidence: 99%